2006
DOI: 10.1007/s00586-006-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

The femoro-sacral posterior angle: an anatomical sagittal pelvic parameter usable with dome-shaped sacrum

Abstract: IntroductionThe interdependence between the pelvis and the sagittal spinal curvatures is obvious. The leading part of the pelvic sagittal anatomy in this orientation was well established by Duval-Beaupe`re thanks to the description of the angle 'Pelvic Incidence' (PI) [14]. It is the angle between the line perpendicular to the superior plate of the first sacral vertebra (S1) at its midpoint and the line connecting this point to the middle axis of the femoral heads. It is own for every individual and independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
2
54
2
3
Order By: Relevance
“…40,41 A recent review 42 showed that pelvic incidence had been concluded as a predictive factor for spondylolisthesis in some of the published literature. 13,15,39 It had also reported that few studies showed no significant difference between PI of normal and subjects with scoliosis.…”
Section: Discussionmentioning
confidence: 98%
“…40,41 A recent review 42 showed that pelvic incidence had been concluded as a predictive factor for spondylolisthesis in some of the published literature. 13,15,39 It had also reported that few studies showed no significant difference between PI of normal and subjects with scoliosis.…”
Section: Discussionmentioning
confidence: 98%
“…Third, we did not image the entire spine; however, we found strong correlations using lumbar images alone. Fourth, the accuracy of measuring sacral slope angles is dependent on the radiographic definition of the anterior part of the sacrum [27]. We did not evaluate the accuracy of methods for measuring pelvic, lumbar, and femoral angles.…”
Section: Discussionmentioning
confidence: 99%
“…We did not evaluate the accuracy of methods for measuring pelvic, lumbar, and femoral angles. The accuracy of the measurements is disputed in the literature, since accuracy is dependent on the ability to identify landmarks in the presence of degenerative diseases of the spine [18,27]. However, excellent intra-and interobserver reliability for measuring sacral slope and lumbar lordosis angles on lateral radiographs has been reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the sagittal plane the curvature is dictated by the wedged shape of the vertebral bodies and intervertebral discs (Masharawi et al. 2008), the pelvic incidence (defined as the inclination of the sacral end‐plate with respect to a line joining the midpoint of the end‐plate to the axis of the hip joints) (Legaye, 2007), and the orientation of the pelvis about the hip joints (Day et al. 1984).…”
Section: Discussionmentioning
confidence: 99%